1994
DOI: 10.1007/bf00763220
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function studies of [2Fe-2S] ferredoxins

Abstract: The ability to overexpress [2Fe-2S] ferredoxins in Escherichia coli has opened up exciting research opportunities. High-resolution x-ray structures have been determined for the wild-type ferredoxins produced by the vegatative and heterocyst forms of Anabaena strain 7120 (in their oxidized states), and these have been compared to structural information derived from multidimensional, multinuclear NMR spectroscopy. The electron delocalization in in these proteins in their oxidized and reduced states has been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 87 publications
4
101
0
Order By: Relevance
“…First, the cross-linking of Fd I to FNR was not prevented by the elimination of the carboxyl group at position 92, but its rate was decreased in the case of Fd-E92K in keeping with the lower affinity for FNR of this mutant as measured by the Kd of the complex (Table 3). Second, the role for the sidechain of Glu92 according to the three-dimensional structure of the cyanobacterial ferredoxin (Holden et al, 1994) should be to stabilize the [2Fe-2S] binding loop through hydrogen bonding to the Ser45 side-chain. Indeed, beside a modification of the redox potential of the iron-sulfur cluster in the Glu92 mutants, small changes in their EPR spectra were also observed , suggesting a perturbation of the iron-sulfur cluster environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the cross-linking of Fd I to FNR was not prevented by the elimination of the carboxyl group at position 92, but its rate was decreased in the case of Fd-E92K in keeping with the lower affinity for FNR of this mutant as measured by the Kd of the complex (Table 3). Second, the role for the sidechain of Glu92 according to the three-dimensional structure of the cyanobacterial ferredoxin (Holden et al, 1994) should be to stabilize the [2Fe-2S] binding loop through hydrogen bonding to the Ser45 side-chain. Indeed, beside a modification of the redox potential of the iron-sulfur cluster in the Glu92 mutants, small changes in their EPR spectra were also observed , suggesting a perturbation of the iron-sulfur cluster environment.…”
Section: Discussionmentioning
confidence: 99%
“…In the chloroplast-type ferredoxins, the acidic cluster is fairly well conserved: Glu92 (spinach protein sequence numbering) is strictly conserved ; Glu93 is conservatively substituted by Asp in two cases or changed to Gln; Glu94 is more variable, but in such a way that an acidic residue is always present at the positions 93 or 94 (SwissProt Data Bank). Whereas ferredoxins from higher plants have not been structurally characterised, the three-dimensional structure of ferredoxins from cyanobacteria has been determined both by X-ray crystallography and NMR (Holden et al, 1994). Recently, sitedirected mutagenesis studies on cyanobacterial ferredoxins have been reported (Holden et al, 1994;Schmitz et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These H bonds are part of an evolutionarily conserved hydrogen bonding pattern believed to stabilize the [2Fe-2S] binding loop by tethering it to the short C-terminal a-helix (Holden et al, 1994). Preliminary X-ray crystallographic data on the E94K mutant (B.L.…”
Section: Mutations At E94 and E95 In Vfdmentioning
confidence: 99%
“…The wt stability of Vfd mutant E95K can be rationalized in terms of what is known about the environment of this residue. Because the electron density from the E95 side chain is at the protein surface and is not well defined in the electron density map derived from X-ray analysis (Holden et al, 1994), this residue is solvent exposed and appears not to participate in specific interactions with the rest of the protein. …”
Section: Nh2mentioning
confidence: 99%